Penerapan Pijat Oksitosin Lavender Terhadap Volume ASI pada Ibu Pasca Melahirkan - Agustini Liviana Dwi Rahmawati; Nilam Cahyaning Setyoningrum (Indonesian Journal of Nursing Scientific, 2025)
Background: Postpartum mothers may inhibit breastfeeding due to delayed initiation of breastfeeding, postoperative pain, and psychological stress. These conditions can inhibit lactational exposure and reduce maternal confidence in breastfeeding. Purpose: the purpose of this study was to describe the implementation of lavender oxytocin massage on milk production in postpartum mothers. Methods: The research design used was descriptive analysis in a case study involving three postpartum mothers with ineffective breastfeeding problems in Delima Ward Rumah Sehat Untuk Jakarta. The intervention involved a daily 15-20 minutes oxytocin massage combined lavender oil, administered for three consecutive days. Result: The results showed breast milk production initiated in large amounts between 3 days after intervention. Mother S increased from 10 ml to 80 ml, Mother F from 15 ml to 95 ml, and Mother P from 40 ml to 105 ml after the intervention. The oxytocin massage stimulates the release of prolactin hormone especially when combined with lavender oil for relaxing postpartum mother to breastfeeding outcomes. Conclusion: Lavender oxytocin massage is effective in increasing breast milk volume and has a positive impact on the physical and psychological comfort of postpartum mothers.